Peningkatan Keterampilan Guru dalam Mengembangkan Desain Model Pembelajaran berorientasi HOTS Berbasis Learning Management System bagi Guru Sekolah Dasar di Kota Surakarta - Sajidan Sajidan; Idam Ragil Widianto Atmojo; Matsuri Matsuri; Fadhil Purnama Adi; Roy Ardiansyah; Dwi Yuniasih Saputri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The purpose of this service activity is to improve teacher skills in developing HOTS-oriented learning model designs based on the Learning Management System (LMS) for elementary school teachers in Surakarta City. Participants in the community service activity totaled 30 teachers consisting of 10 class teachers of SD ICT Al-Abidin, 10 class teachers of SD Ta'mirul Islam Surakarta, and 10 class teachers of SD Muhammadiyah 1 Ketelan Surakarta. The method of implementing this service uses training and mentoring. The instrument for evaluating the improvement uses a test and is analyzed descriptively. The results of this service activity show that there is an increase in teacher skills after participating in the training activity. Teacher skills increase in the experience aspect in designing HOTS-oriented learning models, teacher experience in designing activities to develop HOTS, and in processing features contained in the Learning Management System. Based on the results of limited trials, the HOTS-oriented learning model design in the Learning Management System achieves an average student passing scores of 83%.